2018
DOI: 10.13031/trans.12555
|View full text |Cite
|
Sign up to set email alerts
|

Single-Parameter Thin-Layer Drying Equations for Long-Grain Rice

Abstract: Abstract. The use of multiple parameters in thin-layer drying equations makes it difficult to compare and quantify the impact of drying air temperature, relative humidity, and other factors on the drying characteristics of an agricultural crop. In this study, two single-parameter equations are proposed to quantify thin-layer drying characteristics of contemporary long-grain rice cultivars grown in the Mid-South U.S. Drying runs were first performed to obtain drying curves for cultivar ‘Roy J’ under 18 air cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Contrarily, for XL753, the HRY for microwave‐dried rice with 20% initial HMC was significantly lower than the control sample. The differences in the two cultivars may be due to their inherent biological variations in size, shape, morphology, and kernel composition (Bruce et al, 2021; Prakash & Siebenmorgen, 2018). The pubescent nature (hair‐like microstructure on the hull) of long grain hybrids may also influence their drying property and HRY (Atungulu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, for XL753, the HRY for microwave‐dried rice with 20% initial HMC was significantly lower than the control sample. The differences in the two cultivars may be due to their inherent biological variations in size, shape, morphology, and kernel composition (Bruce et al, 2021; Prakash & Siebenmorgen, 2018). The pubescent nature (hair‐like microstructure on the hull) of long grain hybrids may also influence their drying property and HRY (Atungulu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Once the n value was fixed at the mean value (n = 0.784), the experimental data were fitted again for each drying condition in order to re-adjust the k value. This modification was proposed by Prakash and Siebenmorgen [63] and it was concluded that the model predictability was slightly reduced whereas the complexity of the generalized model was condensed. Hence, a variation of k between 3.660 × 10 −3 and 2.998 × 10 −2 for T = 10-50 • C, 9.820 × 10 −3 and 8.025 × 10 −3 for RH = 20-60% and 8.904 × 10 −3 and 9.940 × 10 −3 for v = 0.15-1.00 ms −1 was ascertained accordingly.…”
Section: Generalized Modelmentioning
confidence: 99%
“…The thin layer is characterized as a very thin grain surface that shows a maximum exposure in relation to the air flow (Bala, 2017). The models developed by Lewis, Page, Thompson, Overhults, Brooker, and Midilli were chosen for the analysis in this work because they showed good results in previous studies on grains of different types (Liu et al, 2015;Souza et al, 2015;Sun et al, 2016;Abasi et al, 2017;Nejadi & Nikbakht, 2017;Jian & Jayas, 2018;Prakash & Siebenmorgen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the model showed satisfactory data, it is limited, as the diffusion of the product's internal moisture was neglected. The drying of different rice cultivars was analyzed, using the Page, Lewis, and Midilli's models, which were considered valid for predicting the drying of rice after adjustments (Prakash & Siebenmorgen, 2018). The drying of saffron roots was evaluated using eleven exponential models that showed statistically satisfactory results in relation to the experimental data (Karthikeyan & Murugavelh, 2018).…”
Section: Introductionmentioning
confidence: 99%